Gravity-magnetic appraisal of the southern part of the Cauvery Basin, Eastern Continental Margin of India (ECMI): evidence of a volcanic rifted margin - Ganguli, Shuva Shankha; Pal, Sanjit K. (Frontiers in Earth Science, 2023)
The Cauvery sedimentary basin of India, a part of the Eastern Continental Margin of India (ECMI), has evolved as a consequence of its breakup from East Antarctica in the early Cretaceous. This study covers approximately 10,000 km2 in the southern part of the Cauvery basin. A total of 5,161 gravity-magnetic observations were made in an area bounded by 78°–79°E longitude and 9°–10°N latitude. The gravity anomaly map shows a dominant NE-SW trend with a total relief of 83 mGal from −77 mGal to 6 mGal. The map reveals very prominent NE-SW trending linear gravity high bands and two circular/elliptical gravity lows around Madurai and Ramanathapuram, respectively. The residual gravity map reveals NE-SW trending alternative bands of gravity highs and lows, revealing a ridge-depression structure. The gravity modeling shows the presence of underplated material, which may be related to magmatic activity during the Cretaceous. The magnetic map reveals two prominent E-W trending linear structures, which probably represent the disposition of a shear zone under the Cauvery Basin. Based on the filtered magnetic and gravity map, we have prepared an interpreted basement geology map. The magnetic map and residual gravity map suggest that the basement rock of the basin is crystalline (granite/gneiss) and may not comprise a high-grade metamorphic rock Eastern Ghat Orogeny.